A feasibility study in establishing "Cyber Quest.Com" in Barangay San Francisco,Gen.Trias, Cavite - Mercado, Daniel Jr. R., author; Nueva, Annalyn R., author; Jistre, Mabel A., author; Ventura, Elizabeth A., adviser; Berbie Lucila C., member; Dulce, Nora N., member; Alvarez, Nestor M., chairman (Rosario, Cavite : Cavite State University-CCAT Campus, 2005)
Thesis Abstract
A Project Feasibility Study (BSBM)--Cavite State University-CCAT Campus, 2005.
Includes bibliographical references and appendices.
In English text
Keywords: New business enterprises; Small business; Internet business